2017
DOI: 10.1038/s41598-017-09155-8
|View full text |Cite
|
Sign up to set email alerts
|

Significance of penile hypersensitivity in premature ejaculation

Abstract: To assess the correlation between penile hypersensitivity and premature ejaculation (PE), a total of 420 consecutive subjects attending our andrologic clinic for suspected PE were enrolled. The entire cohort was asked to complete the self-report intravaginal ejaculation latency time (IELT) by stopwatch. According to the IELT, the subjects were classified into 3 groups. Vibratory thresholds were recorded at the glans penis and penile shaft using a biothesiometer. We found that vibratory thresholds in the glans … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(16 citation statements)
references
References 33 publications
2
14
0
Order By: Relevance
“…A recent study did not detect any significant difference in penile sensitivity between men with or without premature ejaculation or delay ejaculation . However, our previous study also confirmed the sensitization of penile sensation with a relative large sample size . The mechanism of peripheral nerve sensitization in the penis is also indicated by the effectiveness of local anesthetics in the treatment of premature ejaculation .…”
Section: Introductionsupporting
confidence: 81%
“…A recent study did not detect any significant difference in penile sensitivity between men with or without premature ejaculation or delay ejaculation . However, our previous study also confirmed the sensitization of penile sensation with a relative large sample size . The mechanism of peripheral nerve sensitization in the penis is also indicated by the effectiveness of local anesthetics in the treatment of premature ejaculation .…”
Section: Introductionsupporting
confidence: 81%
“…Blood tests were performed for each participant including hormone profile values, fasting blood glucose, and lipids. Laboratory examinations were conducted at the laboratory of the Second Hospital of Shandong University, using a biochemical analyzer (Modular Analytics, Roche, Mannheim, Germany) . Blood samples from each participant were collected from the antecubital vein at 8:00 AM after 12 hours of fasting, and then, all samples were drawn into tubes coated with ethylene diamine tetraacetic acid (EDTA).…”
Section: Methodsmentioning
confidence: 99%
“…The increased sensitivity of the penis significantly reduces the IELT, further leading to PE. Our previous clinical research showed that penile hypersensitivity was a factor contributing to short intravaginal ejaculation latencies (Guo et al., 2017). Many studies have attempted to treat PE by reducing penile hypersensitivity (Dai et al., 2019; Liu et al., 2019).…”
Section: Discussionmentioning
confidence: 99%